1995
DOI: 10.1111/j.1445-5994.1995.tb01893.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal haemorrhage following coronary artery bypass grafting

Abstract: Upper GI haemorrhage following CABG is relatively frequent. It is usually secondary to duodenal ulceration. Endoscopy is a safe procedure in this patient group. Mortality did not differ between index patients who suffered a UGI haemorrhage and controls undergoing CABG who did not bleed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…Indeed, the average age of the patients is elevated and in our study was 68.8 yrs ± 10.2 years, which is similar to what others have reported [7]. An antecedent history of ulcer disease, although not noted in our study, has been reported to be a risk factor for the development of UGI bleeding in past analyses [12].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, the average age of the patients is elevated and in our study was 68.8 yrs ± 10.2 years, which is similar to what others have reported [7]. An antecedent history of ulcer disease, although not noted in our study, has been reported to be a risk factor for the development of UGI bleeding in past analyses [12].…”
Section: Discussionsupporting
confidence: 79%
“…Some have suggested a lesser incidence of bleeding duodenal ulcers in postoperative vascular patients [19]. However, in most reports, commonly reported lesions at endoscopy have included, as in our series, gastroduodenal ulcers or erosions and esophagitis [12,[20][21][22]. These findings are similar to those noted for in-hospital and outpatient patients presenting with an episode of NVUGIB [5,10].…”
Section: Discussionsupporting
confidence: 78%
“…Based on this study's analysis, the risk of UGIB in patients undergoing TAVR (2.0%) is notably higher than other cardiac patients. For example, the incidence of UGIB following coronary artery bypass grafting (CABG) has been described to be 0.5% . This study shows that the risk of UGIB following TAVR has an increase in absolute risk of 1.5% compared to CABG.…”
Section: Discussionmentioning
confidence: 79%
“…Dysphagia has been noted in up to 50% of patients who remain intubated more than 48 hours, which results in a delay in resumption of oral feeding and a prolongation of hospital stay. 274,275 The causative mechanism is usually decreased blood flow, mucosal ischemia, and a hypoperfusion/reperfusion injury that may be exacerbated by increased gastric acidity. The occurrence of pharyngeal dysfunction in the absence of common contributing factors (TEE, ventilation) has been ascribed to a new neurologic deficit.…”
Section: Gastrointestinal Complicationsmentioning
confidence: 99%